Learning to draw is learning to see: a comprehensive review of art and design practices in higher education / Muhammad Abdullah ... [et al.] - Abdullah, Muhammad; Khairani, Mohd Zahuri; Vincent Amos, Fareez; Abdul Aziz, Mohd Nasiruddin; Ramlie, Mohd Khairulnizam (Universiti Teknologi MARA, Perak, 2024)
Practises related to learning to draw and learning to see are valuable knowledge in higher education. The drawing process can lead to improvements in visual perception, cognitive skills, and creative thinking abilities. This research presents a case for the integration of drawing practises in higher education, arguing that it can enhance students' ability to think creatively and visually, both in academic and professional pursuits. Through a comprehensive contextual analysis of the literature review from 2019 until 2023, this research examines the evidence that drawing is produced from observation and considers the wide potential implications of learning in higher education. As a result, a conceptual model is presented to explain the relationship between drawing elements and learning to see. This research concludes with a discussion of the potential benefits of incorporating drawing practises into higher education and the challenges and opportunities involved. Overall, this research contributes to supporting comprehensive art and design practises for learning to draw and learning to see and highlights the potential value of drawing in higher education.